A green and efficient vortex-assisted liquid-phase microextraction based on supramolecular solvent for UV–VIS determination of nitrite in processed meat and chicken products. (1st December 2020) - Altunay, Nail; Elik, Adil
Highlights: The first report on the use of SUPRAS as extraction solvents for nitrite. UV–VIS spectrophotometric were used for the determination of nitrite. Important variables affecting the recovery of nitrite were scrutinized. The proposed method provides very low limit of detection. Abstract: This paper describes a simple, efficient and rapid analytical method for extraction and determination of nitrite in meat and chicken products by vortex-assisted supramolecular solvent-based liquid phase microextraction (VA-SUPRAS-LPME) prior to spectrophotometric detection. The SUPRAS was rapidly formed by the addition of a colloidal decanoic acid suspension to tetrahydrofuran (THF). The validation studies were carried out in terms of linearity, limit of detection (LOD), limit of quantitation (LOQ), matrix effects, robustness, uncertainty measurement, precision, accuracy, and certified reference material (CRM) analysis using optimized experimental conditions. The LOD, LOQ, linearity and matrix effect were 0.035 ng mL −1, 0.1 ng mL −1, 0.1–300 ng mL −1, and 9.6% respectively, with high preconcentration factor (2 0 0). The method was successfully applied for the determination of nitrite in processed products. Moreover, the results obtained by the proposed method were compared to the standard Griess method, and showed no significant differences in term of Student's t -test.